Music therapy : intimate notes - Pavlicevic, Mercedes (London ; Philadelphia : Jessica Kingsley Publishers, 1999)
The stories and reflections in this book describe powerful encounters between nine music therapists and clients. The stories reveal the passion and integrity of nine music therapists who undergo profound changes as a result of their work. The book provides a lively and informal theoretical foundation, connecting music to our intimate lives.
Intro -- Music Therapy -- Intimate Notes, by Mercédès Pavlicevic -- Acknowledgements -- Introduction -- Finding our Muses -- PART I -- Music Therapy with Children -- Chapter 1: Daniel -- Blossoms and Baptism -- Chapter 2: Wendy -- 'I Used To Be Crying Every Day...' -- Chapter 3: Sinead -- 'Here is my Arm...' -- Chapter 4: Giorgos -- Isolation in a Hospital Ward -- PART II -- Music Therapy with Adults -- Chapter 5: Martha -- Working with Wellness -- Chapter 6: Mary and Steve -- Creativity and Terminal Illness -- Chapter 7: Shireen -- Into the Void of Brain Injury -- Chapter 8: Miriam and Seaun -- Danger and Intimacy in a Secure Unit -- Chapter 9: Olive and Jim -- Senility and Wisdom -- Conclusion -- Intimate Notes -- Further Reading -- Blank Page.
Includes bibliographical references (page 145).
Print version record.
eBooks on EBSCOhost
Keywords: Music therapy -- Case studies; Music therapists -- Biography; Musicothérapie -- Études de cas; Musicothérapeutes -- Biographies; Creative Therapy (Eg Art, Music, Drama); MEDICAL -- Pharmacology; Music therapists; Music therapy; Biographies; Case studies; Biographies; Biographies